ESCREVENDO CARTAS PARA UM PROGRAMA DE TV: CARTAS NA CONTEMPORANEIDADE - Castro, Ana Caroline Silva de (2009)
Letters are one of the oldest long distance communication ways ever known. Beyond that, for centuries, treaties and studies on how letter are and how they should be written have been made. This study focus on letters sent to the TV show Globo Rural, from Globo Television, in 2005, in it s 25th birthday. Firstly, thru a 418 letters database, the identity and demands from viewers that had written to the show were delineated. It was perceived, among other issues, that beyond the people living in rural areas and that keep elation with the field, many viewers of urban and professional areas of not-agriculture areas of knowledge also enter in contact with the program through letters. Secondly, through intentional choices in a qualitative way, with no intention of generalizing, some actual characteristics on writing letters, has been discussed. Comparing with former treaties dating from the Ancient Age, it can be concluded that the analyzed letters still keep many traces defined since then.(AU)